Study of expression of genes potentially responsible for reduced fitness in patients with myotonic dystrophy type 1 and identification of new biomarkers of testicular function. Issue 1 (16th December 2019) - Ergoli, Manuela; Venditti, Massimo; Picillo, Esther; Minucci, Sergio; Politano, Luisa
Abstract: Myotonic dystrophy type 1 (DM1) is a multisystemic disorder caused by trinucleotide CTG expansion in DMPK gene, often affecting the neighboring genes. Endocrine system is involved, resulting in hypogonadism and reproductive abnormalities, but molecular mechanisms underlying the reduced fertility observed in DM1 are very complex and partially unknown. To better characterize these mechanisms, an analysis of sperm parameters and anti‐Müllerian hormone (AMH) values was performed in 20 DM1 patients. About 50% of them showed hypoposia and azoospermia; the remaining, despite an adequate volume of ejaculate, had oligo‐astheno‐teratozoospermia. Interestingly, the lowest AMH levels better correlated with the main sperm alterations. The pattern of expression of DMPK, SIX5, and RSPH6A genes, evaluated by quantitative reverse transcription polymerase chain reaction, showed a substantial reduction of the expression in both peripheral blood and in seminal plasma of patients, compared to controls. An impairment of testis‐specific RSPH6A protein expression and localization was observed in sperm protein extracts by WB analysis and in isolated spermatozoa by immunofluorescence. These results support the hypothesis that CTG expansion also affects the expression of neighboring genes and contributes to gonad defects observed in DM1, suggesting the possibility of using them as markers for normal fertility in humans.